DNAzyme–gold nanoparticle-based probes for biosensing and bioimaging. Issue 41 (21st September 2020) - Hu, Ling; Fu, Xiaoyi; Kong, Gezhi; Yin, Yao; Meng, Hong-Min; Ke, Guoliang; Zhang, Xiao-Bing
Abstract : The design and applications of DNAzyme–gold nanoparticle-based probes in biosensing and bioimaging are summarized here. Abstract : The deoxyribozyme (DNAzyme) is a specific nucleic acid with high catalytic activity in the presence of coenzyme factors. Because of its good programmability, high stability and excellent activity, DNAzyme is considered to be a promising material in many fields, such as environmental monitoring, food regulation, biosensing and gene therapy. Gold nanoparticles exhibit excellent photoelectric properties, and can also provide DNAzyme with enhanced cell transfection and excellent resistance to nuclease degradation. Therefore, DNAzyme–gold nanoparticle complexes have attracted much attention in many areas, particularly in biosensing and bioimaging. In this review, we first provide a brief introduction of the structure and catalytic activity of DNAzymes, as well as several methods for preparing DNAzyme–gold nanoparticles. Then, the discussion focuses on applications of DNAzyme–gold nanoparticle-based probes in biosensing and bioimaging in recent years (especially in the past five years). Based on their output signals, these sensors are divided into fluorescence sensors, colorimetric sensors, electrochemical sensors, photoelectrochemical sensors and other sensors. Finally, we discuss several challenges and opportunities in this emerging field.